Avaliação da distribuição e mobiblidade de elementos traço em sedimentos da bacia hidrográfica do Rio São Francisco - Patricia Sueli de Rezende (2009)
Sediments have organic and inorganic contaminants retention capability. These properties are depending on physical-chemical characteristics, like mineral composition, granulometry, ionic exchange capacity and organic matter contents. Sediments compose a dynamic system, with high reactivity and frequent ionic exchanges with aqueous phase. The pollutants accumulation in sediments occurs by electrostatics interactions, Al, Fe and Mn oxides adsorption, organic matter complexation, and variations as temperature, pH, and redox potential can remove these pollutants. On this form, the interaction between immobilized contaminants and sediments is crucial for prediction the availability and mobility of them to the aquatic ecosystem. In this work, sediments samples were collected in 28 points from São Francisco River Basin. They were submitted to three different sample preparation procedures: aqua regia pseudo-total extraction, sequential extraction according to BCR protocol, and partial extraction using HCl 1 mol L-1 solution. The environmental availability of As, Cd, Cr, Cu, Fe, Hg, Mn, Ni, Pb and Zn were evaluated after all procedures. About 20% of the accomplished analyses using aqua regia pseudo-total extraction presented superior values to the established by Resolution 344/2004 from CONAMA. Arsenic, chromium and lead corresponded to 70% of the high concentrations observed superior to the established by legislation. Results obtained after sequential extraction procedure pointed out that Cd e Zn are the most available to the water flow in the studied area. They presented high release in the first stage from sequential procedure, which are lixiviated elements that present high availability. Cadmium presented extraction values in a range of 83 to 139%, and zinc in a range of 18 to 156%, when compared to the pseudo-total digestion. For partial extraction using HCl 1,0 mol L-1 solution, Cd and Zn were the elements more easily labiles, they presented extraction in a range to 84 to 112% to Cd, and between 27 and 122% to Zn. Samples that presented the lowest As and Hg concentrations on the pseudo-total extraction were the samples that presented the highest contents extracted by diluted HCl solution. The samples that presented the highest Hg concentrations were submitted to the thermodesorption coupled to the atomic absorption spectrometry to speciation. Only Hg (II) specie was identified, in spite of the contamination was due to Hg(0), showing the natural oxidation phenomenon of Hg on the sediments. The results presented environmental degradation by inorganic pollutants relatively high in 21% of the sampling points, indicating that these contaminations are from anthropogenic activities.